Implementasi kebijakan vaksinasi covid-19 di Indonesia: narrative review - Sutari Sutari; Haerawati Idris; Misnaniarti Misnaniarti (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: Currently the Covid-19 pandemic is still happening which has resulted in an increase in the number of deaths. The number of Covid-19 cases in Indonesia is more than 2.5 million with the death toll reaching 25,000. To prevent the transmission of Covid-19, the government has made a policy with a vaccination program. Methods: The research method used is narrative review, searching for articles using an internet database with the keywords COVID-19 vaccination in Indonesia with a time limit of 2020 to 2021. The search results obtained 10 articles which were then analyzed using context, input, process and product (CIPP) on the implementation of the Covid-19 vaccination. The obtained literatures were synthesized using the narrative method by grouping the extracted data that was similar to the measured results to answer the research objectives. Results : The results of the study indicate that the existence of a policy and the government's pick-up effort is expected to support the success of vaccination. However, the implementation of the covid-19 vaccination in Indonesia has not been optimal due to factors; lack of public participation due to doubts about the